Reservation‐Urban Comparison of Suicidal Ideation/Planning and Attempts in American Indian Youth. (24th March 2020) - Manzo, Karen; Hobbs, Gerald R.; Gachupin, Francine C.; Stewart, Jera; Knox, Sarah S.
ABSTRACT: BACKGROUND: Our aim was to identify sex‐ and location‐specific risk factors for suicide ideation/planning and attempts among American Indian youth. METHODS: Biennial data for 6417 American Indian high school students attending reservation and urban schools were extracted from the Montana volunteer sample Youth Risk Behavior Survey data for pooled years 2003 to 2011. Logistic regression was used to identify sex‐ and school location‐specific risk behaviors and psychosocial factors for past 12‐month ideation/planning and past 12‐month attempts. RESULTS: Contrary to our hypothesis, the prevalence of ideation/planning and attempts did not significantly differ between reservation/urban location; however, risk factors associated with suicidality did. Sadness/hopelessness was associated with both outcomes for all groups. However, violent victimization was associated with both outcomes only among girls. Lack of school safety was associated with attempts but not ideation/planning among all students. There were distinct differences in risk factors associated with both outcomes among boys. CONCLUSIONS: The results indicate differences and similarities in risk behaviors and psychosocial factors associated with suicidality by sex and reservation/urban setting. Implications include screening potentially at‐risk students for depression, violent victimization, substance use, and school safety and use of the findings by tribal and school programs in designing prevention and intervention programs.